PEMBINAAN MANAJEMEN INTERNET SEHAT DAN AMAN PADA MASYARAKAT KELURAHAN TANJUNG SARI KECAMATAN BELAKANG PADANG - Nainggolan, Nora Pitri; Sari, Intan Utna; Purba, Mortigor Afrizal (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
The rapid development of the internet today has not been accompanied by an understanding of healthy and safe use of the internet, especially for internet users among children in their teens. The internet is an important human need for both children and parents. Through the internet, we will be able to get information very quickly and can be accessed from anywhere. So it is not surprising that the development of the internet in Indonesia has also experienced an extraordinary increase because of its many benefits. Even though the internet has a positive impact on everyday life, it can also pose extraordinary threats to a family. Every parent definitely wants their child not to be trapped in the world of the internet which tends to be detrimental. Therefore, parents should supervise their children's activities on the internet. Being alert to all children's surfing activities in cyberspace is important because of the wide variety of information available, especially negative information. This negative information cannot be prevented, but we can only filter it either by reminding our children or by installing security software on our computers. Through this coaching, it is hoped that every family will be able to use the internet healthily, and parents will also be able to apply limits on the gadgets and laptops they will use so that children can surf the internet safely.